How do I find the equation of a perpendicular bisector of a line segment with the endpoints #(-2, -4)# and #(6, 4)#?

2 Answers
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

4

This answer has been featured!

Featured answers represent the very best answers the Socratic community can create.

Learn more about featured answers

Jan 23, 2016

Answer:

#x+y-2=0#

Explanation:

Here's how.

You need to find the slope of the segment since it is the negative reciprocal of the slope of the bisector.
Another one you will have to find is the midpoint of the segment because the bisector will pass trough that point.

If you have those two, you can now determine the equation of the perpendicular bisector using point-slope form of a line.

Let:
#m_s =>#slope of the segment
#m_b=>#slope of the bisector
#(x_1, y_1)=>(-2, -4)#
#(x_2, y_2)=>(6, 4)#
#M(x_m, y_m)=>#midpoint of segment

Solving for the slope of the segment:

#m_s=(y_2-y_1)/(x_2-x_1)=(4-(-4))/(6-(-2))=8/8=1#

Solving for the slope of the bisector:

#m_b=-1/m_s=-1/1=-1#

Solving for the midpoint of the segment:

#x_m=(x_1+x_2)/2=(-2+6)/2=2#

#y_m=(y_1+y_2)/2=(4-4)/2=0#

#M(2, 0)#

Solving for the equation of the segment:

POINT-SLOPE FORM

#y-y_m=m_b(x-x_m)#

#y-0=-1(x-2)#

#y=-x+2 " " larr #slope-intercept form

#x+y-2=0" " larr # standard form

Was this helpful? Let the contributor know!
1500
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

2
Jul 16, 2016

Answer:

#x+y-2 = 0#

Explanation:

Let #(x,y)# be any point on the perpendicular bisector. From elementary geometry, we can easily see that this point must be equidistant from the two points #(-2,-4) and (6,4)#. Using the Euclidean distance formula gives us the equation

#(x+2)^2 + (y+4)^2 = (x-6)^2 + (y-4)^2 #

This can be rewritten as

#(x+2)^2 - (x-6)^2 = (y-4)^2-(y+4)^2#

Using #a^2 -b^2 = (a+b)(a-b)#, this simplifies to

#8(2x-4) = -8*2y# which simplifies to

#x+y-2 = 0#

Was this helpful? Let the contributor know!
1500
Trending questions
Impact of this question
2577 views around the world
You can reuse this answer
Creative Commons License